ENHANCING CREATIVITY BASED ON LOCAL POTENTIAL THROUGH TIKTOK SOCIAL MEDIA FOR STUDENTS AT MADRASAH ALIYAH KARYA MADANI, WEST BANDUNG REGENCY - Candra, Muhammad Fazri; Ersyad Muttaqien, Muhammad (LPM Universitas Pasundan, 2025)
This community service activity aims to enhance the creativity of students at Madrasah Aliyah Karya Madani, West Bandung Regency, in utilizing TikTok social media. The high level of internet usage opens up new professional opportunities, one of which is becoming a content creator. However, students still face challenges such as limited knowledge about the professions of content creators and affiliates, a lack of awareness regarding the positive benefits of social media, and insufficient technical skills in content production. The Community Service Team from the Communication Science Study Program, Universitas Pasundan, took the initiative to carry out a program with the theme “Enhancing Creativity through TikTok Social Media for High School Students at Madrasah Aliyah Karya Madani, West Bandung Regency.” This program applied a contextual approach, beginning with educational sessions on the professions of content creators and affiliates on TikTok, followed by simulations and training on becoming content creators and affiliates. The program continued with sessions on how to produce content on TikTok and concluded with mentoring to ensure optimal results. The outcomes of the activity indicated improvements in students’ understanding, technical skills, and ethical awareness in creating TikTok content based on local potential. Keywords: Training, Content Creator, TikTok, High School Students